Language use at home and performance in English composition in multilingual Ghana - Ahadzi, Sika; Ameka, Felix K.; Essegbey, James (AAeO - Afrikanistik-Aegyptologie-Online, 2015)
Ghana has witnessed a recurrent debate on the usefulness of indigenous Ghanaian languages in childhood education. It is assumed that using the mother tongue as a Medium of Instruction (MOI) during the early years improves children’s ability to acquire knowledge and other languages. Not everybody subscribes to this view though. There are those who feel that a solid start in English offers children a better chance of succeeding in school and in their careers. Presently, some parents who subscribe to the latter view have taken the extra step of stopping the use of indigenous Ghanaian languages at home. This paper presents the results of our investigation into whether the home language practices of Ghanaian students have any impact on their performance in English written argumentative discourse. The results are based on an analysis of an assigned essay of 92 students from one of Ghana’s best senior high schools. We then correlated their per¬formance with responses they gave to a questionnaire interrogating their background and language use at home. While some speak the native language at home, others grew up speaking exclusively English. We show that students who combine English and native Ghanaian languages at home performed better than those who used only English or only Ghanaian languages.